Beneficial Endophytic Bacterial Populations Associated With Medicinal Plant Thymus vulgaris Alleviate Salt Stress and Confer Resistance to Fusarium oxysporum - Abdelshafy Mohamad, Osama Abdalla; Ma, Jin-Biao; Liu, Yong-Hong; Zhang, Daoyuan; Hua, Shao; Bhute, Shrikant; Hedlund, Brian P.; Li, Wen-Jun; Li, Li (Frontiers in Plant Science, 2020)
As a result of climate change, salinity has become a major abiotic stress that reduces plant growth and crop productivity worldwide. A variety of endophytic bacteria alleviate salt stress; however, their ecology and biotechnological potential has not been fully realized. To address this gap, a collection of 117 endophytic bacteria were isolated from wild populations of the herb Thymus vulgaris in Sheikh Zuweid and Rafah of North Sinai Province, Egypt, and identified based on their 16S rRNA gene sequences. The endophytes were highly diverse, including 17 genera and 30 species. The number of bacterial species obtained from root tissues was higher (n = 18) compared to stem (n = 14) and leaf (n = 11) tissue. The endophytic bacteria exhibited several plant growth-promoting activities in vitro, including auxin synthesis, diazotrophy, phosphate solubilization, siderophore production, and production of lytic enzymes (i.e., chitinase, cellulase, protease, and lipase). Three endophytes representing Bacillus species associated with T. vulgaris such as EGY05, EGY21, and EGY25 were selected based on their ex-situ activities for growth chamber assays to test for their ability to promote the growth of tomato (Solanum lycopersicum L.) under various NaCl concentrations (50–200 mM). All three strains significantly (P < 0.05) promoted the growth of tomato plants under salt stress, compared to uninoculated controls. In addition, inoculated tomato plants by all tested strains decreased (P < 0.05) the activity of antioxidant enzymes (superoxide dismutase, catalase, and peroxidase). Six strains, representing Bacillus and Enterobacter species EGY01, EGY05, EGY16, EGY21, EGY25, and EGY31 were selected based on in vitro antagonistic activity to F. oxysporum for pot experiments under salt stress. All tested strains reduced the disease severity index (DSI) of tomato plants at all tested salt concentrations. Gas-chromatography/mass-spectrometry analysis of cell-free extracts of B. subtilis (EGY16) showed at least ten compounds were known to have antimicrobial activity, with the major peaks being benzene, 1,3-dimethyl-, p-xylene, dibutyl phthalate, bis (2-ethylhexyl) phthalate, and tetracosane. This study demonstrates that diverse endophytes grow in wild thyme populations and that some are able to alleviate salinity stress and inhibit F. oxysporum pathogenesis, making them promising candidates for biofertilizers and biocontrol agents.